(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
CdZnXS1-X thin films with different composition have been deposited on glass substrate by by the spray pyrolysis method at RT using CdCl2 (0.1M),ZnCl2(0.1M)and H2NCSNH2(0.1M)solution and a substrate temperature of ( 400Â±20Â°C). X-ray diffraction studies reveal that the films are polycrystalline in nature with hexagonal structure and preferential orientation along (002) . The grain size of the films is found to increase formÂ (37.397 to 46.902) nm with increasing Zinc concentration while the strain and the dislocation density of the films are found to decrease from (7.15 to 4.54) 10 4 rad and from (3.82 to 1.93) 10 14 lines.m-2 respectively . TheÂ transmittanceÂ spectrumsÂ ofÂ CdZnxS1-xÂ thinÂ filmsÂ reveal very pronounced interference effects for photon energies below the fundamental absorption edge by exhibiting interference pattern . The optical energy gap for CdZnxS1-x thin films increases and shifts towards the UV regionÂ as theÂ Zn concentration in the films increased . Â